Performance and Stability Improvement of Inverted Perovskite Solar Cells by Interface Modification of Charge Transport Layers Using an Azulene–Pyridine Molecule. Issue 2 (14th December 2022) - Tzoganakis, Nikolaos; Feng, Boxu; Loizos, Michalis; Chatzimanolis, Konstantinos; Krassas, Miron; Tsikritzis, Dimitris; Zhuang, Xiaodong; Kymakis, Emmanuel
Abstract : Herein, an azulene–pyridine molecule (AzPy) is implemented in inverted perovskite solar cells (PSCs) for increasing the power conversion efficiency (PCE) and the stability of the devices. The first goal is achieved by depositing a thin layer of AzPy on top of the hole charge transport layer (HTL). The surface engineering of HTL with AzPy improves the perovskite layer formation, thus increasing light absorption and reducing bulk nonradiative recombination while protecting the perovskite from degradation species from the HTL. This approach increases the mean PCE by approximately 6%. The second goal of improving the stability of the devices is mainly achieved by replacing the hydrophilic bathocuproine (BCP) with the more hydrophobic AzPy. By the development of an AzPy layer over the electron transport layer (ETL), the stability of the PSCs is increased under ambient conditions and thermal or light stress, without affecting the PCE. The two proposed interface engineering approaches are both implemented in the device in conjunction with the perovskite surface treatment with n ‐hexylammonium bromide, resulting in devices that deliver a PCE of 20.42% and increased thermal and light stability, thus retaining 90% of their initial PCE for more than 1200 h under ambient conditions. Abstract : Surface engineering of hole and electron transport layers with an azulene–pyridine molecule and in conjunction with perovskite treatment by an alkylammonium salt increases power conversion efficiency to 20.42% and enhances the stability of the inverted perovskite devices.